Pengaruh Gaya Kepemimpinan Dan Hubungan Interpersonal Terhadap Kinerja Pegawai (Studi Kasus Kantor Kecamatan Jatibarang Kabupaten Brebes) - Chaerul Anam; Muhammad Syaifulloh; Azizah Indriyani (Kampus Akademik Publiser, 2024)
This research was conducted to find out whether there is a positive influence of leadership style on employee performance, the influence of interpersonal relationships on employee performance simultaneously on employee performance in the Jatibarang sub-district office. The method used is quantitative with the aim of this research being to determine whether there are two or more variables, as well as how far there is a correlation between the variables studied. The population used in this research was all 30 employees in the Jatibarang sub-district office. The sampling technique uses a total sampling technique or the entire population of objects is used as a sample. The data analysis technique uses the SPSS version 16 program. What is tested is the validity and reliability test, the classic assumption test which consists of the multicollinearity test, heteroscedasticity test, Kolmogorov normality test. descriptive analysis test. Verification analysis tests include multiple linear regression analysis tests and coefficient of determination tests. Hypothesis testing is using the t test and f test. The results of this research are 1) leadership style has a significant and positive effect on employee performance. It is known that the significance value for the influence of x1 on y is 0.001 < 0.05 and the calculated t value is 3.902 > t table 2.048. 2) Interpersonal relationships have a significant and positive effect on employee performance. It is known that the significance value for the influence of x2 on y is 0.001 < 0.05 and the calculated t value is 3,544 > t table 2,048. 3) simultaneously, the variable leadership style and interpersonal relationships simultaneously on employee performance is 0.000 < 00.05 and the calculated F value is 21,341 > f table 3.354.